Fidel : a critical portrait - Szulc, Tad, 1926-2001 (Avon Books, 1987)
Never before has any biographer had such close access to Fidel Castro as did Tad Szulc. The outcome of a long, direct relationship, this riveting portrait reveals astonishing and exclusive information about Cuba, the revolution, and the notorious, larger-than-life leader who has ruled his country with an iron fist for more than forty years. Only Tad Szulc could bring Fidel to such vivid life--the loves and losses of the man, the devious tactics of the conspirator, the triumphs and defeats of the revolutionary leader who challenged an American president and brought the world to the brink of nuclear disaster. From Jesuit schools to jungle hideouts and the Palace of the Revolution, here is FIDEL...THE UNTOLD STORY